Difficulties in Diagnosis and Operation Associated With Lumbar Intradural Disc Herniation: A Case Report: Lumbar intradural disc herniation - T. Le, Hieu; Dinh, Hoai; H.T. Pham, Quynh; D. Tran, Hoang; T. Nguyen, Minh (International Clinical Neuroscience Journal, 2023)
Intradural disk herniation (IDH) represents an uncommon instance of disk degeneration. The surgical treatment of IDH, preoperative, and intraoperative diagnosis are difficult. The present case report highlights the difficult parts of diagnosis and surgery. A 44-year-old man presented with lower back pain radiating to his right leg. A disk protruding into the ventral dural sac and exhibiting the hawk-beak sign was discovered by MRI. The dorsal side was exposed and incised during L3/4 laminectomy, a puncture on the ventral side was detected, and subsequently, three fragments extending into the dura sac were discovered. The defect was corrected and completed internal fixing was done. Pathology identified it as nucleus pulposus tissue. At one-month follow-up, he was able to walk normally. An incredibly uncommon form of disc degeneration is lumbar IDH. MRI can assist in the diagnosis, however, surgical investigation and pathology are necessary for an accurate diagnosis.